2016
DOI: 10.1017/s0022029915000692
|View full text |Cite
|
Sign up to set email alerts
|

Minor milk constituents are affected by protein concentration and forage digestibility in the feed ration

Abstract: The present study was conducted in order to investigate if selected minor milk components would be indicative for the nutritional situation of the cow. Forty-eight dairy cows were offered a high digestible ration vs. a lower digestible ration combined with 2 protein levels in a 4 × 4 Latin square design. Milk glucose, glucose-6-phosphate, cholesterol, triacylglycerides (TAG), uric acid and β-hydroxybutyrate (BHBA) were measured and correlated mutually and towards other milking parameters (yield, h since last m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
5
12
2
Order By: Relevance
“…The energy boost from PG might have stimulated the microbial turnover in the rumen, thereby more uric acid is formed by degradation of microbial purines in DNA and RNA (Chibisa et al 2009; Stentoft et al 2015). A comparable situation was seen when high density energy rations were tested against low energy density rations (Larsen et al 2016). In contrast, it has been hypothesised that PG allocation would reduce ruminal microbial protein production (Chibisa et al 2009).…”
Section: Resultssupporting
confidence: 53%
“…The energy boost from PG might have stimulated the microbial turnover in the rumen, thereby more uric acid is formed by degradation of microbial purines in DNA and RNA (Chibisa et al 2009; Stentoft et al 2015). A comparable situation was seen when high density energy rations were tested against low energy density rations (Larsen et al 2016). In contrast, it has been hypothesised that PG allocation would reduce ruminal microbial protein production (Chibisa et al 2009).…”
Section: Resultssupporting
confidence: 53%
“…The glucose 6 P content of the milk in the M group was higher compared to milk from the A group. The same tendency was observed by Larsen et al (2016) who reported significantly higher levels (P < 0.001) of both monosaccharides in cows on a highly digestible ration compared to a lower digestible ration. The present goats were in positive energy balance and no significant differences were observed for the plasma metabolites related to fat mobilization, i.e.…”
Section: Metabolites In Milk Urine and Plasmasupporting
confidence: 84%
“…In cows, reduced UA concentrations in urine were related with reduced nitrogen flow to the duodenum and hence a reduced production of microbial protein in the rumen ( Tas and Susenbeth, 2007 ). Recently, however, Larsen et al (2016) found increased UA concentration in milk when cows were fed highly digestible feed versus a low-digestibility feed. The present finding of a reduced UA concentration in milk from PDS+ sows remains unclear, but against this background, it might be speculated that the intestinal function or health of PDS+ sows could be compromised.…”
Section: Discussionmentioning
confidence: 99%